Interaction Analyses of the Integrin β2 Cytoplasmic Tail with the F3 FERM Domain of Talin and 14-3-3ζ Reveal a Ternary Complex with Phosphorylated Tail - Chatterjee, Deepak (2017)
Integrins, which are heterodimeric (α and β subunits) signal-transducer proteins, are essential for cell adhesion and migration. β cytosolic tails (β-CTs) of integrins interact with a number of cytosolic proteins including talin, Dok1, and 14-3-3ζ. The formation of multiprotein complexes with β-CTs is involved in the activation and regulation of integrins. The leukocyte-specific β2 integrins are essential for leukocyte trafficking, phagocytosis, antigen presentation, and proliferation. In this study, we examined the binding interactions between integrin β2-CT and T758-phosphorylated β2-CT with positive regulators talin and 14-3-3ζ and negative regulator Dok1. Residues of the F3 domain of talin belonging to the C-terminal helix, β-strand 5, and the adjacent loop were found to be involved in the binding interactions with β2-CT. The binding affinity between talin F3 and β2-CT was reduced when β2 T758 was phosphorylated, but this modification promoted 14-3-3ζ binding. However, we were able to detect stable ternary complex formation of T758-phosphorylated β2-CT, talin F3, and 14-3-3ζ that involved the repositioning of talin F3 on β2-CT. We showed that Dok1 binding to β2-CT was reduced in the presence of 14-3-3ζ and when β2 T758 was phosphorylated. Based on these data, we propose a sequential model of β2 integrin activation involving these molecules. Our study provides for the first time insights toward β2 integrin activation that involves a multiprotein complex.